Fast coding unit decision and mode selection for intra‐frame coding in high‐efficiency video coding. Issue 3 (1st March 2016) - Tseng, Chao‐Feng; Lai, Yen‐Tai
Abstract : High‐efficiency video coding (HEVC) is a new video coding compression standard. As the successor to H.264/AVC, it provides better performance and supports higher resolution. However, the encoding complexity increases drastically. One of the major reasons is that the coding unit (CU) in HEVC is multi‐sized and adjustable rather than fixed as in H.264. In addition, the number of prediction modes used in intra‐frame coding is expanded from 9 to 35. The authors analysed the statistical correlations of CU depth to the deviation of pixels in the largest coding unit (LCU) and rate‐distortion cost (RDcost). Accordingly, a fast CU decision method is proposed, which contains two steps: first, the depth to begin searching is determined according to the deviation of the LCU and then splitting the current CU further is decided according to RDcost. For intra‐prediction, we also propose a fast mode selection method to reduce complexity. This method can quickly determine the modes for rate‐distortion optimisation when the combination of most probable modes reveals the pattern direction. Software simulations show that the proposed methods reduce encoding time by more than 50% with an average of 1.4% increase of BD‐rate compared to reference software HM12.0.